Familial Alzheimer's disease-linked presenilin mutants and intracellular Ca2+ handling: A single-organelle, FRET-based analysis. (May 2019) - Greotti, Elisa; Capitanio, Paola; Wong, Andrea; Pozzan, Tullio; Pizzo, Paola; Pendin, Diana
Graphical abstract: Highlights: FAD PS2, but not PS1, decrease the Ca 2+ content of the main intracellular stores. FAD PS2 mutants partially block SERCA activity. FAD PS1 and PS2 mutants reduce SOCE by decreasing the expression level of STIM1. Abstract: An imbalance in Ca 2+ homeostasis represents an early event in the pathogenesis of Alzheimer's disease (AD). Presenilin-1 and -2 (PS1 and PS2) mutations, the major cause of familial AD (FAD), have been extensively associated with alterations in different Ca 2+ signaling pathways, in particular those handled by storage compartments. However, FAD-PSs effect on organelles Ca 2+ content is still debated and the mechanism of action of mutant proteins is unclear. To fulfil the need of a direct investigation of intracellular stores Ca 2+ dynamics, we here present a detailed and quantitative single-cell analysis of FAD-PSs effects on organelle Ca 2+ handling using specifically targeted, FRET (Fluorescence/Förster Resonance Energy Transfer)-based Ca 2+ indicators. In SH-SY5Y human neuroblastoma cells and in patient-derived fibroblasts expressing different FAD-PSs mutations, we directly measured Ca 2+ concentration within the main intracellular Ca 2+ stores, e.g., Endoplasmic Reticulum (ER) and Golgi Apparatus (GA) medial- and trans-compartment. We unambiguously demonstrate that the expression of FAD-PS2 mutants, but not FAD-PS1, in either SH-SY5Y cells or FAD patient-derived fibroblasts, is able to alter Ca 2+ handling of ER and medial-GA, but not trans-GA, reducing, compared to control cells, the Ca 2+ content within these organelles by partially blocking SERCA (Sarco/Endoplasmic Reticulum Ca 2+ -ATPase) activity. Moreover, by using a cytosolic Ca 2+ probe, we show that the expression of both FAD-PS1 and -PS2 reduces the Ca 2+ influx activated by stores depletion (Store-Operated Ca 2+ Entry; SOCE), by decreasing the expression levels of one of the key molecules, STIM1 (STromal Interaction Molecule 1), controlling this pathway. Our data indicate that FAD-linked PSs mutants differentially modulate the Ca 2+ content of intracellular stores yet leading to a complex dysregulation of Ca 2+ homeostasis, which represents a common disease phenotype of AD.